Integration of Four Pillars of Schools of Quality into Accreditation as a Reference for Improving the Quality of Early Childhood Education - Ardhian, Nur Luthfi; Supriyanto, Achmad; Timan, Agus; Rawanti, Sri; Hardiyanti, Waode Eti (International Research-Based Education Journal, 2024)
This article aims to analyze the implementation of the concept and principle of Total Quality Management (TQM) and try to integrating Four Pillars of Schools of Quality (FPSQ) into playgroup/kindergarten’s system, which used the accreditation standard as the standard to improving school’s of quality. The method used in this article is a literature review based on observation and interview results in this school. The analysis results show that unconsciously this playgroup/kindergarten has implemented concept and principle in achieving its accreditation, and from FPSQ indicators can be said that these schools have applied the first step in total quality improvement. Based on the results, it can be assumed that integration FPSQ into the school’s system would form a quality school culture that not only refers to the achievement of accreditation’s score.